Perancangan Rekam Medis Berbasis Web pada Praktek Umum Dokter Adrianus Riyanto - Elisabeth Elisabeth (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2013)
Along with the development of technological information nowadays, and many problemsthat occur at The General Practitioner Doctor Adrianus Riyanto’s Practice so the medicalrecords data which used to be recorded by conventional way finally are grown into an applicationthat is called medical records application. This application was started by analyzing the problemby interviewing the doctor, nurse, and patient. This aplication was built by HypertextPreprocessor language and MySQL which the output will be implemented and tested by interviewprocess. The reachable result indicates that medical records development assist to improveproductivity and efficiency work from general practitioner.